The Impact That Students Develop From Using Digital Wallets - Hasnawati. A. Dg. Maserre; Widia adisti Saliani; Jesica Revani Aulia putri (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
The invention of electronic wallets, or "E-wallets," is the outcome of fintech's expansion. An indication that more people are beginning to use digital wallets for everyday transactions is the rise in electronic money transfers. In order to ascertain the variables influencing engineering students' intents to utilize digital wallets, this study used a quantitative methodology. This study's population and sample consisted of engineering students in Indonesia that utilize digital wallets. The sample was drawn using a probability sampling approach called simple random sampling, which was successful in gathering up to 266 respondents, and an analysis method that made use of SPSS. The study's findings demonstrate how interest in utilizing digital wallets is influenced by perceived utility and convenience. In this study, however, interest in using digital wallets is unaffected by risk perception.